Pediatricians' Knowledge of Children's Oral Health: A National Survey - Abrar Alanzi; Saleh Muhammad; Anfal Faridoun; Aisha Alterkait (Elsevier, 2023)
ABSTRACT: Background: A high percentage of dental caries (∼70%) was reported amongst 4- and 5-year-old Kuwaiti kindergarten children. Parents contact paediatricians several times during the child's early life. Paediatricians can play an important role in improving the oral health of their patients. The objective of the study is to evaluate the knowledge level and awareness of paediatricians and paediatric residents regarding children's oral health in Kuwait. Methods: A national cross-sectional survey was distributed to paediatricians and paediatric residents practicing in Kuwait. Data concerning demographic variables, knowledge on dental caries preventive measures, current anticipatory guidance, and experience with dental problems and oral care were collected using online and paper-based surveys. Results: A total of 230 participants completed the survey, with a response rate of 50.1%. Most respondents (81%) had frequently noticed dental caries in children in their practice. Two-thirds of respondents felt confident in detecting dental caries. However, more than two-thirds were unfamiliar with preventive dental practices and the management of dental trauma. Only 16.5% of the respondents got a satisfactory knowledge score on the preventive measure questions, and nearly 51% had satisfactory knowledge on the recent anticipatory guidance questions. No significant correlations were found between gender or years of practice and knowledge scores. Respondents' confidence in detecting caries was significantly associated with the knowledge score of the anticipatory guidance (P = .003). Fewer than half of the respondents considered prescribing sugar-free syrup (47.4%) and counselled patients regarding the use of mouthguards during sports for schoolchildren (39%). Conclusions: The majority of paediatricians have adequate knowledge of the current anticipatory guidance of oral health issues, but they have insufficient knowledge of oral preventative measures and dental trauma. Adequate education and training in oral health are highly recommended.